The Effect of Some Variables on Neonatal Deaths in The Neonatal Intensive Care Unit in Al-Kut City, 2024: A Comparative study between two hospitals - Al-Arkwze, Wria Abbas; Mansur, Mathil Alwan; Abdulazeez, Hussein Atta; Hama al-Jaf, Ali Ismael (Journal of Neonatal Surgery, 2025)
The newborn period is defined as the first 28 days of life. In practice, however, sick or very immature infants may require neonatal care for many months. Study aims: to identify the variables affecting neonatal mortality in the neonatal intensive care unit at Al-Zahra and Al-Kut hospitals, and compare the results between them. Methodology: An analytic cross-sectional study was conducted with a purposive sample of sterile preterm infants to identify the impact of various variables on neonatal mortality in the leading hospitals of Al-Kut District. Data were collected from records for the year 2024. Results: In Al-Kut Hospital, the p-value of both variables, weeks of pregnancy and type of birth, was 0.004 and 0.04, respectively; the two variables have a significant effect on the cause of death, the rest of the variables (Gender, Weight, Birth was single or multiple, and the Mother's age) had no significant impact. In Al Zahraa Hospital, all variables do not have a significant effect on the cause of death. Conclusion: There is a difference in the effect of the variables under study between the two hospitals on the cause of death of premature infants.